Psilorhynchus kaladanensis, a new species (Teleostei: Psilorhynchidae) from Mizoram, northeastern India - Lalramliana, Lalramliana; Lalnuntluanga, Lalnuntluanga; Lalronunga, Samuel (Zootaxa, 2015)
Psilorhynchus kaladanensis, a new psilorhynchid, is described from the Kaladan basin of Mizoram, India. The new species is diagnosed by having the following combination of characters: caudal fin with small but distinct dark brown triangular spot at mid-base, slightly elongated dark mark near base of lower lobe, indistinct V-shaped vertical bar across center, dark brown oblique bar across fin anterior to center; absence of scales on mid-ventral region between pectoral fins; anteriormost branchiostegal ray greatly reduced in length; 32–33 total vertebrae; 30–32 lateral-line scales; caudal fin with 10+9 principal rays.